EXERCISE CAPACITY IN CHILDREN AND ADOLESCENTS WITH POST-INFECTIOUS BRONCHIOLITIS OBLITERANS: A SYSTEMATIC REVIEW - Camila Menna Barros Rodrigues; Daniele Schiwe; Natália Evangelista de Campos; Fabiana Niederauer; João Paulo Heinzmann-Filho (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To evaluate exercise capacity in children and adolescents with post-infectious bronchiolitis obliterans. Data source: This is a systematic review based on data from PubMed, Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS), Scientific Electronic Library Online (SciELO), and Physiotherapy Evidence Database (PEDro). We used the following search strategy: "Exercise capacity OR Exercise Test OR Physical fitness OR Functional capacity OR Six-minute walk test OR Shuttle walk test OR Cardiopulmonary exercise test AND Bronchiolitis obliterans." We selected studies that evaluated exercise capacity through maximal/submaximal testing in children and adolescents with post-infectious bronchiolitis obliterans, and no other associated disease. We searched articles in English, Portuguese, and Spanish, without restrictions regarding the period of publication. The methodological quality was assessed by the Agency for Healthcare Research and Quality (AHRQ) protocol. Data synthesis: Out of the 81 articles found, only 4 were included in this review. The studies totaled 135 participants (121 with post-infectious bronchiolitis obliterans and 14 healthy), with sample sizes between 14 and 58 subjects. All patients underwent spirometry to evaluate pulmonary function, indicating an obstructive ventilatory pattern. Among them, 3/4 had their physical performance assessed by the six-minute walk test and 2/4 by the cardiopulmonary exercise testing. These test results were compared to those of a control group (1/4) and presented as percentage of predicted and/or in meters (3/4). Lastly, 3/4 of the studies showed reduced exercise capacity in this population. The studies included were classified as having high methodological quality. Conclusions: Findings of the study demonstrate that children and adolescents with post-infectious bronchiolitis obliterans have reduced exercise capacity.